Los responsables de los impresos en Costa Rica, 1900-1930 - Vega Jiménez, Patricia (2004)
This article is aimed at identifying the people responsible of editing and printing the newspapers in Costa Rica between 1900 and 1930, such as editors, directors, managers, chroniclers, and commentators. This social group, comprised by individuals with diverse interests in the academic, political, religious, and economic fields, is particularly concerned about the importance of forming public opinion in the Costa Ricans of the period.